Eczema herpeticum: A medical emergency in patients with atopic dermatitis - Vera-Kellet, Cristián (IDCases, 2019)
We describe the case of a 13-year-old girl with atopic dermatitis (AD) and severe asthma that presented to the Dermatology clinic with a pruritic skin rash, which appeared concomitantly to common cold symptoms. On examination, there are erythematous, umbilicated papules and vesicles, some with erosions and crusting, surrounding the mouth and areolas; a few lesions are visible on the forearms. The mucous membranes were unaffected, the patient was afebrile, and no lymphadenopathies were present. A diagnosis of eczema herpeticum (HE) was suspected, and a direct fluorescent antibody test was positive for herpes simplex virus. Even when the clinical presentation is characteristic, the eruption might be confused with other infections like impetigo and primary varicella infection. Misdiagnosis can lead to severe complications, including bacteremia and death. EH is considered a medical emergency, and the index of suspicion for this infection should be high among clinicians. Prompt treatment with oral acyclovir should be initiated; in cases of severe disease or immunocompromised patients, hospitalization for systemic antivirals is required. If EH is recognized early it is easily and effectively treated. Any patient with pre-existing skin disease and acute "blistering" should be examined to rule out EH.